Hubungan Edukasi Bidan pada Kala IV Persalinan dengan Ambulasi Dini di Puskesmas Tanggul Tahun 2023 - Hamid, Lilis Setyorini; Sugijati, Sugijati; Restanty, Dian Aby (Puslitbang Sinergis Asa Professional, 2024)
The phenomenon that exists in post partum mothers after the fourth stage of labour, is they still do not perform early ambulation for physiological reasons, namely the body is still experiencing fatigue, pain in the birth canal, so they are afraid to move the body, worrying about bad consequences. Mothers under 20 years of age are slower to respond to early ambulation guidance due to emotional factors of fear and anxiety, compared to those aged 20-30 years who are more emotionally stable. However, when the mother is over 35 years old, there may be a delay in responding to early ambulation due to physiological factors the body experiences fatigue and recovers more slowly than at less than 35 years of age. The general objective of this study was to determine the existence of a relationship between midwifery education in the fourth stage of labor and early ambulation at the Tanggul Health Center in 2023. The research design used a correlation analytic survey, non-probability sampling with purposive sampling technique, data testing with chi square. The results of the study were: from the education of midwives who delivered all stages of ambulation, post partum who carried out early ambulation 3 people (10.0%), late 2 people (6.7%), while education of midwives who delivered part of the stages, post partum who carried out early ambulation 13 people (43.3%), late 12 people (40%). The p-value > 0.05 (alpha), Ho is accepted, meaning that there is no relationship between Midwife Education and Early Ambulation. Conclusion: Post partum midwife education delivery with all stages or not in accordance with the stages still gets the attention of post partum mothers, but because there are many factors that influence the behavior of early ambulation in postpartum, so not all postpartum mothers can do early ambulation.